Pengaruh Perilaku Konsumen Terhadap Penggunaan Uang Elektronik (Dompet Digital) Sebagai alat Pembayaran pada Masa Pandemi Covid – 19 di Kota Medan - Maria Kristina Situmorang (Maneggio: Jurnal Ilmiah Magister Manajemen, 2021)
This study aims to determine and analyze the influence of consumer behavior on the use of electronic money (digital wallets) as a means of payment during the Covid-19 pandemic in the city of Medan. The population in this research was 12,185 people. The sample in this study was 100 people. The data collection technique used was a questionnaire. The data analysis technique used is multiple regression analysis. The results showed that there was an effect of consumer behavior on the use of electronic money (digital wallets) as a means of payment during the Covid-19 pandemic in the city of Medan